Twin deficits revisited : a role for fiscal institutions? - Afonso, António (2018)
We revisit the twin deficit relationship for a sample of 193 countries over the period 1980-2016, using a panel fixed effect (within-group) estimator, bias-corrected least-squares dummy variable, system GMM, and common correlated effects pooled estimation procedures. The analysis accounts also for the existence of fiscal rules in place, their features, and their interaction with the budget balance. In the absence of fiscal rules, the twin deficit hypothesis is confirmed. The size of the estimated coefficient on the budget balance is between 0.68 and 0.79. However, the existence of fiscal rules strongly reduces the effect of budget balance on the current account balance (the coefficient is reduced to 0.1). In fact, the twin deficits relationship does not hold with some specific kinds of rules: debt rules, rules with monitoring of compliance, as well as budget balance rules and debt rules in emerging market economies and lowest income countries, and in the post-crisis period.